Incorporation of the noncoding roX RNAs alters the chromatin-binding specificity of the Drosophila MSL1/MSL2 complex. - Li, F.; Schlemann, A.H.; Scott, M.J. (Molecular and Cellular Biology, 2008)
The male-specific lethal (MSL) protein-RNA complex is required for X chromosome dosage compensation in Drosophila melanogaster. The MSL2 and MSL1 proteins form a complex and are essential for X chromosome binding. In addition, the MSL complex must integrate at least one of the noncoding roX RNAs for normal X chromosome binding. Here we find the amino-terminal RING finger domain of MSL2 binds as a complex with MSL1 to the heterochromatic chromocenter and a few sites on the chromosome arms. This binding required the same amino-terminal basic motif of MSL1 previously shown to be essential for binding to high-affinity sites on the X chromosome. While the RING finger domain of MSL2 is sufficient to increase the expression of roX1 in females, activation of roX2 requires motifs in the carboxyl-terminal domain. Binding to hundreds of sites on the X chromosome and efficient incorporation of the roX RNAs into the MSL complex require proline-rich and basic motifs in the carboxyl-terminal domain of MSL2. We suggest that incorporation of the roX RNAs into the MSL complex alters the binding specificity of the chromatin-binding module formed by the amino-terminal domains of MSL1 and MSL2.